Research on Large-Area Blackbody Radiation Source for Infrared Remote Sensor Calibration - Ji, Yalan; Hao, Xiaopeng; Sun, Yandong; Xing, Zhao; Song, Jian; Zhou, Jingjing; Sima, Ruiheng; Sun, Shuangcheng; Wang, Guangjun (International journal of thermophysics, 2022)
Because of the calibration requirements of large-area infrared remote-sensing equipment, a large-area blackbody radiation source with the area of 1.05 m × 1.05 m is developed at the National Institute of Metrology (NIM), China. The temperature range of the blackbody is from room temperature to 573 K. A multiple temperature control technique is employed for improving the temperature stability and uniformity of the blackbody. The effects of the heating zone and material thickness on the temperature uniformity are investigated by thermodynamic simulation, and then the uniformity and stability of the blackbody temperature are tested. Retrieval results illustrate that the temperature uniformity of the blackbody radiation source system is less than ± 0.65 K. The temperature stability of the blackbody at all temperature points is less than 0.1 K in 10 min. The expanded combined standard uncertainty of the blackbody is 0.97 K at 373 K, 1.13 K at 473 K, and 1.53 K at 573 K.